Legal Regulation of the Non-Entrepreneurial Legal Entities’ Status: Foreign Experience - ZELISKO, Alla V.; ZOZULIAK, Olga I.; SISHCHUK, Liliana V. (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018DO - 10.14505//jarle.v9.5(35).36, 2018)
The relevance of the study is due to the fact that the implementation of the task of improving private-law regulation of relations with the participation of non-entrepreneurial legal entities is possible only on the basis of the international experience of the operation of the legal institute. In this context, this article aims to analyze the positive experience of regulating non-entrepreneurial legal entities under the legislation of leading foreign countries. Leading approach to the study of this problem is the comparative method that has afforded revealing peculiarities of regulation of legal entities under consideration within Ukraine and foreign countries. In the article the suggestions for improving the legislation of Ukraine are presented on the basis of foreign experience. The materials of the paper imply the practical significance for the university teachers of the legal specializations.